Influencia del Programa nacional de apoyo directo a los más pobres “JUNTOS” a mujeres beneficiarias del distrito de Paiján – 2018. - Lescano Ponce, Leyla del Carmen (2019)
The thesis report aims to influence the National Program of Executive Support to the poorest “JUNTOS” a women beneficiaries of the district of Paiján - 2018, this replicates the opportunities offered by the program to women Benefits and the influence it has on the optimization of female human capital. A sample of 129 beneficiaries of the PNADP “JUNTOS” was taken, with the inclusion criteria of the leading mothers of each sector and those who have children of school age. Methods such as: ethnographic, inductive, deductive, statistical and analytical are used; The techniques of review of bibliographic sources, observation, interview and survey and the instruments such as the observation guide, interview guide, registration forms and questionnaire. In chapter I; The problematic reality arises. In chapter II; The methodology for the compilation of statistical data from sampling, instrument application is presented; In addition to having a support the techniques of observation and interview. In chapter III; The presentation of results and discussion of the research variable is carried out. This research has among its conclusions in the framework of the intervention of the Juntos Program, in the district of Paiján, 93.8% of the women beneficiaries consider that the Juntos Program provides them with the functions of directed towards their person, very much on the part of the stipulated benefits that the Program provides to children, adolescents, pregnant women, and 85.3% of women beneficiaries that when belonging to the Program Juntos.